2016
DOI: 10.1016/j.scr.2016.08.007
|View full text |Cite
|
Sign up to set email alerts
|

Tbx3 fosters pancreatic cancer growth by increased angiogenesis and activin/nodal-dependent induction of stemness

Abstract: Cell fate decisions and pluripotency, but also malignancy depend on networks of key transcriptional regulators. The T-box transcription factor TBX3 has been implicated in the regulation of embryonic stem cell self-renewal and cardiogenesis. We have recently discovered that forced TBX3 expression in embryonic stem cells promotes mesendoderm specification directly by activating key lineage specification factors and indirectly by enhancing paracrine NODAL signalling. Interestingly, aberrant TBX3 expression is ass… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
27
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(27 citation statements)
references
References 66 publications
0
27
0
Order By: Relevance
“…Recent data indicate that non-stem cancer cells can re-enter the stem state and the metastatic disease in patients is concomitant with the appearance of stemness and EMT in these cells 13 . Overexpressed on hematopoietic stem cells with in vivo repopulating activity 6 and subsequently identified as a cancer stem-cell maintenance factor 14 , JAM-A may reprogram lymphoma cells to a de-differentiated stem-like state, contributing to lymphoma progression in DLBCL.…”
Section: Discussionmentioning
confidence: 99%
“…Recent data indicate that non-stem cancer cells can re-enter the stem state and the metastatic disease in patients is concomitant with the appearance of stemness and EMT in these cells 13 . Overexpressed on hematopoietic stem cells with in vivo repopulating activity 6 and subsequently identified as a cancer stem-cell maintenance factor 14 , JAM-A may reprogram lymphoma cells to a de-differentiated stem-like state, contributing to lymphoma progression in DLBCL.…”
Section: Discussionmentioning
confidence: 99%
“…The overexpression of TBX3 has also been positively linked to migration and invasion of pancreatic ductal adenocarcinoma (PDAC). Compared to normal adjacent and healthy donors, PDAC tissue samples had increased levels of TBX3 mRNA and stained positive for TBX3 protein (65). Furthermore, in vitro assays show that overexpression of TBX3 in Pan1 and BxPC3 pancreatic cell lines significantly enhanced their migratory ability and invasion potential and xenotransplantation experiments revealed that TBX3 overexpressing Pan1 and BxPC3 cells induced significantly larger tumours than their controls.…”
Section: Tbx3 In Tumour Formation Invasion and Metastasismentioning
confidence: 96%
“…On the other hand, TBX3 overexpression resulted in a significant increase in CSC numbers, tumoursphere-forming ability and a more than 100-fold increase in tumour-seeding potential in vivo. A recent study by Perkhofer et al also demonstrated that TBX3 overexpressing pancreatic cancer cells had increased sphere-forming ability and that TBX3 induced the CSC phenotype of primary pancreatic cancer cells by regulating NODAL/ACTIVIN signalling through an autocrine positive feedback loop (65). In light of this, it would be interesting to determine whether TBX3 impacts similarly on CSCs in other cancers and if this is an additional mechanism through which it contributes to cancer development and anti-cancer drug resistance.…”
Section: Tbx3 and Cancer Stem Cellsmentioning
confidence: 99%
“…The common gene sets were also listed and sorted in descending order of F-statistics (Supplementary file 8). T-box transcription factor TBX 3 (TBX3), which was the top common candidate, has been previously reported to be associated with TGF-β signaling, angiogenesis and cancer growth (70,71). Enrichment analysis of top genes of all four predicted HCC subtypes showed enrichment of different and specific pathway terms for each subtypes (Figure 10; Supplementary file 9).…”
Section: Identification Of Hcc Subtypes and Their Featuresmentioning
confidence: 98%